THE IMPACT OF LAND SUBSIDENCE ON POPULATION DENSITY AND FLOOD DISASTERS IN SEMARANG CITY - Rahman, Muhammad Farras (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
This study investigates the relationship between land subsidence, population density, and flood disasters in Semarang City using a multiple linear regression approach. Data from 2012 to 2022 include land subsidence rates, population density, and flood inundation heights. Classical assumption tests—Breusch-Pagan for heteroskedasticity, Variance Inflation Factor (VIF) for multicollinearity, and Shapiro–Wilk for normality—were applied to ensure model validity. The results indicate that both population density and flood inundation height exert a positive but statistically insignificant effect on land subsidence. The model explains 57.6% of the variation in land subsidence. These findings suggest that future studies should incorporate additional variables, such as groundwater extraction rates and infrastructure development, to enhance model accuracy and provide a more comprehensive understanding of land subsidence dynamics in coastal urban areas.